Relationship between reflection ability and clinical performance: A cross-sectional and retrospective-longitudinal correlational cohort study in midwifery. Issue 1 (January 2015) - Embo, M.; Driessen, E.; Valcke, M.; van der Vleuten, C.P.M.
Abstract Background increasingly, reflection is highlighted as integral to core practice competencies but empirical research into the relationship between reflection and performance in the clinical workplace is scarce. Aim this study investigated the relationship between reflection ability and clinical performance. Methods we designed a cross-sectional and a retrospective-longitudinal cohort study. Data from first, second and third year midwifery students were collected to study the variables 'clinical performance' and 'reflection ability'. Data were analysed with SPSS for Windows, Release 20.0. Descriptive statistics, Pearson׳s Product Moment Correlation Coefficients (r) and r² values were computed to investigate associations between the research variables. Findings the results showed a moderate observed correlation between reflection ability and clinical performance scores. When adopting a cross-sectional perspective, all correlation values were significant (p<0.01) and above 0.4, with the exception of the third year correlations. Assuming perfect reliability in the measurement, the adjusted correlations, for year 2 and year 3 indicated a high association between reflection ability and clinical performance (>0.6). The results based on the retrospective-longitudinal data set explained a moderate proportion of the variance after correction for attenuation. Finally, the results indicate that 'reflection ability' scores of earlier years are significant related with 'clinical performance' scores of subsequent years. These results suggest that (1) reflection ability is linked to clinical performance; (2) that written reflections are an important, but not the sole way to assess professional competence and that (3) reflection is a contributor to clinical performance improvement. Conclusions the data showed a moderate but significant relationship between 'reflection ability' and 'clinical performance' scores in clinical practice of midwifery students. Reflection therefore seems an important component of professional competence.